An Organic Mixed‐Valence Ligand for Multistate Redox‐Active Coordination Networks. (13th March 2018) - Ha, Joo Yeon; Koo, Jin Young; Ohtsu, Hiroyoshi; Yakiyama, Yumi; Kim, Kimoon; Hashizume, Daisuke; Kawano, Masaki
Abstract: The multistate redox‐active/multi‐interactive ligand 5, 5′, 8, 8′‐tetra(4‐pyridyl)‐2, 2′‐(1, 4‐phenylene)bis‐1 H ‐perimidine (H2 TPP) was designed and synthesized. H2 TPP undergoes four one‐electron oxidation steps, and was used for the preparation of a multistate redox‐active coordination network in a solid–liquid interface reaction using molten Cd 2+ salts. The multiple redox states of H2 TPP were confirmed spectroscopically by stepwise four‐electron oxidation. Spectroscopic analysis indicated that the mixed‐valence states of the ligand are class II on the UV/Vis/NIR timescale and borderline class II/class III on the ESR timescale. Abstract : Ein redoxaktives Koordinationsnetzwerk wurde in einer lösungsmittelfreien Reaktion aus einer Metallschmelze und dem redoxaktiven Liganden H2 TPP gewonnen. Aufgrund der zwei redoxaktiven Zentren im H2 TPP‐Liganden können Ligand und Netzwerk unterschiedliche Redoxzustände annehmen.